Empowerment of PKK mothers through seaweed-based culinary diversification training in the Coastal Area of Salemo Island - Alimuddin Sa’ban Miru; Faizal Amir; Darmawang; Siti Hadijah; Bakhrani A. Rauf (Abdimas Polsaka, 2026)
This community service activity aimed to increase the added value and economic independence of coastal communities through training in diversifying seaweed-based culinary products. The program was implemented on Salemo Island, Mattiro Bambang Village, Pangkajene and Islands Regency, involving the Independent PKK Mothers Group and the Reski Bersama Seaweed Fishermen Group as partner communities. A participatory approach was applied to ensure active involvement of participants throughout the program, including socialization, technical training in culinary processing, production assistance, and evaluation of outcomes. The training focused on developing innovative seaweed-based food products, such as seaweed meatballs, seaweed nuggets, seaweed barongko, and doi-doi chips made from a seaweed mixture. The results demonstrated a significant improvement in participants’ skills, with approximately 85% of participants able to independently produce processed seaweed products after the training. Product diversification successfully increased the economic value of seaweed, transforming it from a raw material into value-added culinary products with an average selling price of IDR 15,000 per package. In addition to economic benefits, the activity strengthened women’s participation in the productive economy and facilitated the formation of community-level group-based culinary businesses. The findings indicate that seaweed-based culinary diversification training is an effective strategy for enhancing creativity, increasing household income, and promoting economic independence among coastal communities. Furthermore, this program presents strong potential for replication in other archipelagic and coastal regions with similar socio-economic and resource characteristics